The Influence of Local Culture on MSME Accounting and SDG Attainment in Tangerang - Lawita, Florencia Irena; Ario Wicaksono, Dading Damas; Putri, Vallerie Redyna; Orlanda, Rosalyn (OGZ Research & Publishing, 2025)
Objective : This study aims to analyze how local culture influences accounting practices in Micro, Small, and Medium Enterprises (MSMEs) in Tangerang and how it contributes to achieving the Sustainable Development Goals (SDGs). Methods : Using a qualitative approach with in-depth interview methods with MSME actors, it was found that cultural values such as cooperation, kinship, deliberation, and trust are the basis for business decision making and financial management. Research results : The results of the study indicate that local culture-based accounting practices support economic empowerment, social inclusion, and sustainable development, but also face challenges in terms of accountability and digitalization.